Das Saxhorn Adolphe Sax' Blechblasinstrumente im Kontext ihrer Zeit - von Steiger, Adrian; Allenbach, Daniel; Skamletz, Martin (Musikforschung der Hochschule der Künste Bern, 2020)
2014 was the bicentenary of Adolphe Sax's birthday. The Bern University of the Arts (HKB) took this opportunity to take a closer look at Sax and his time, especially from the point of view of his brass instruments and especially the saxhorns. The fact that research into historically informed performance practice is interested in 19th century music and instruments is nothing new. What is new, however, is the insight into the essential role that military music played in European musical life at that time. Reflection of this can be found in their staging in the form of incidental music in numerous operas of the time. Adolphe Sax's family of saxhorns played a vital role in the military music of those years - first in France and subsequently in other countries - and their descendants still form the backbone of the instrumentation of many today's brass band. The aim of the research group was to shed light on the repertoire, playing technique, construction, history and musical and historical contexts of the saxhorn using a multidisciplinary approach. Involved were music research, organology, restoration and numerous active musicians. The articles of almost all researchers familiar with the subject make this volume more than a research report, as it contains the current state of knowledge about the saxhorn.